LABOUR RELATIONS’ TRANSFORMING: CHALLENGES AND OBJECTIVES DURING THE TRANSITION PERIOD - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
Post-industrial global transformations include the transformation of labour relations. The labour dimension is a significant component of social change. Optimizing the course of change involves taking into account changes not only at the micro, but also at the macro level [1-5]. At the same time, the perception and evaluation of activities are historical; ideas about the fruitfulness, the productive power of labour are changeable. The economy is included as a subsystem in its organic social environment. For example, a resource-oriented economy cannot but recognize the primary importance of environmental factors of security and development of society, in particular, when studying the validity of the use of technologies. The technical and technological content of the process, replacing the performance of muscle-energy functions with various aggregates, allows (and makes it effective) to concentrate human efforts on creative tasks. At the same time, the growing tendencies do not at all mean an indispensable rejection of the achievements of Modernity and Tradition; they do not cross out their potentials. On the contrary, new facets of their combination and activation are opening up. But they manifest themselves differently in forms specific to each cultural and civilizational world. And the more fully the local conditions of activity are taken into account during the transition period, the more impressive the result can be achieved [6-17]. Thus, the paradigm features in the transformations of the socio-political order are superimposed on the attitude of man and society to the labour sphere, expanding interest in other areas of self-expression. Systemically, we are talking, first of all, about the factors of the importance of labour in society, external to the economy, about working conditions (external factors of the labour process), factors of labour as such and its quality, as well as factors of attitude to work and the qualities of an employee. Organizational and managerial relations bind, girdle and permeate all these levels together. Moreover, the prerequisites have been formed for creativity to become a concrete-universal process of self-disclosure of the masses from an element of strictly individual leisure, non-labour, a private hobby. If earlier a person, as a rule, was realized within the strict framework of a life path predetermined by birth, today, on a social scale, freedom of choice in the production of meanings has replaced the former freedom from choice with relegation to animal-thing reproduction [18-27]. The formation of an attitude to work adequate to the era on a social scale and the consolidation in society of the personal interest in the success of hyper-industrialization require a complex change in the conditions, process, subject-object relations in the production sphere.